Psychological Distress Among General Adult Population Of Kathmandu Valley - Joshi, Devavrat; Sharma, Pawan; Shrestha, Kenison (Journal of Psychiatrists’ Association of Nepal, 2021)
Introduction: A large proportion of the population in the community with psychological distress goes unnoticed. This study was done to assess the psychological distress among adult population of urban area of the Kathmandu Valley. Material And Method: The study was conducted among 280 individuals of age 18 years and above. Samples were conveniently selected from passersby in front of Mental Hospital, Lagankhel on World Mental health day 2018. The Nepali translated version of the General Health Questionnaire-12 (GHQ-12) was used to assess the psychological distress among the study participants. Results: Majority of the participants had low psychological distress (62.86%) followed by typical (12.86%), more than typical (9.29%), evidence of psychological distress (5.71%) & severe distress (8.93%). 23.93% of the participants had psychological distress which needed attention. Conclusion: The psychological distress is a major public health concern in our study population. Focused interventions to improve the mental health of population are required to decrease the level of psychological distress among the general population.